Generatory obrazu AI – geneza, sposób działaniai tworzenie obrazów religijnych - Janowski, Paweł (Społeczeństwo, 2024)
The paper discusses the origins and functioning of artificial intelligence generators, with a particular focus on the Stable Diffusion model. The author demonstrates how successive milestones in the development of artificial intelligence have shaped the current form of the most popular solution for generating religious images. The paper also highlights the issue of generating images with religious content.